The beauty of frost: nano-sulfur assembly via low pressure vapour deposition. Issue 88 (18th September 2015) - Wang, Yu; Chen, Lu; Scudiero, Louis; Zhong, Wei-Hong
Abstract : A low pressure vapour deposition (LPVD) method is proposed as a solvent-free strategy for fabrication of various sulfur-based nanomaterials. Abstract : A low pressure vapour deposition (LPVD) technique is proposed as an environmentally friendly, cost-effective and versatile strategy for fabrication of sulfur nanomaterials. By controlling the characteristics of the deposit substrate for the LPVD, various sulfur-based nanomaterials have been obtained through a substrate-induced self-assembly process.